Growth and instability of rice production: a district level analysis in West Bengal, India - Jambhulkar, Nitiprasad Namdeorao; Mondal, Biswajit; Bisen, Jaiprakash; Pradhan, Asit Kumar (ORYZA-An International Journal of Rice, 2023)
West Bengal is the largest rice-producing state in the country. It contributes significantly to the national production pool and is one of the important rice consuming state. It is essential to study the growth pattern of rice production in the state. The district wise information of growth rate and instability is not available. Also the association of growth rate and instability has not been studied. Hence the present study was conducted to compute the district wise growth rate and instability in the area, production and yield of rice in West Bengal state and to examine the association between growth rate and instability. The district-wise data on rice was sourced from the Directorate of Economics and Statistics, Ministry of Agriculture and Farmers Welfare, Government of India for the period 1983-84 to 2019-20. The data has been divided into five periods for analysis. Compound annual growth rate and Cuddy-Della Valle Instability index have been computed for the five periods. The instability was divided into five classes. These classes are very low instability, low instability, medium instability, high instability and very high instability.The highest growth rate for area and production was recorded in Nadia district during period I (1983-34 to 1989-90) while the highest growth rate for yield was recorded in South Dinajpur district during period IV (2010-11 to 2019-20). The growth rate for production and yield was positive for all the districts during periods IV (2010-11 to 2019-20) and V (1983-84 to 2019-20). Only one district recorded a negative growth rate for production during period I (1983-84 to 1989-90) and for yield during the period I (1983-34 to 1989-90), III (2000-01 to 2009-10) and IV (2010-11 to 2019-20). The instability varied from 0.63 to 26.57 percent in area, 1.49 to 19.46 percent in production and 0.70 to 45.95 per cent in yield across the districts over five periods.None of the districts recorded very high instability for area, production and yield; high instability for area and production; and medium instability for yield.Most of the districts showed very low instability for area and yield during periods I (1983-34 to 1989-90), II (1990-91 to 1999-2000), III (2000-01 to 2009-10) and IV (2010-11 to 2019-20); and low instability during period V (1983-84 to 2019-20). For production, the highest number of districts recorded low instability during periods I (1983-34 to 1989-90), III (2000-01 to 2009-10), and V (1983-84 to 2019-20) and very low instability during period II (1990-91 to 1999-2000) and IV (2010-11 to 2019-20). The growth in area is moving around zero, which indicates little scope in area expansion. The increase in rice demand can achieved through introduction of new high yielding varieties and application of site specific crop management techniques. For this a comprehensive database may be developed at disaggregated level to implement the policy at district level in West Bengal.